SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DRONE BERKAMERA BERBASIS WEB DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Muchtar, Yuda Abidin; Putri, Riana Defi Mahadji (Jurnal Sistem Komputer, 2021)
Nowadays, a decision support system for drone selection is needed to help commoners when choosing drone based on their needs. Decision support system for drone selection uses simple additive weighting (SAW) method to provide the best alternative based on the importance of several criteria such as camera resolution, video recording resolution, flight time, control distance, battery charging time, speed and price. Waterfall development method is used to make decision support system for drone selection. The purpose of this research is to make decision support system for drone selection with camera built-in by using simple additive weighting (SAW) method. Three experts and five users have done the feasibility test of decision support system for drone selection. Expert test result in percentage is 86% under â€œVery Goodâ€ category and user test result in percentage is 84.4% under â€œVery Goodâ€ category.